轮式装载机驱动桥壳疲劳失效预测模型研究 - 邓先智 (Jixie chuandong)
Aiming at the problem of the fatigue failure of the wheel loader drive axle housing,by using fatigue failure theory,the theoretical and finite element modeling of wheel loader drive axle housing work characteristic is carried out.The law of fatigue failure of wheel loader is studied,a calculation model to predict drive axle housing fatigue failure is proposed.The results show that as computing model considers the random load spectrum and the corrected stress fatigue curves,the wheel loader drive axle failure model fit the actual,the wheel loader drive axle wheel rim section dramatic change location exists stress concentration regularity,the first six orders natural frequency values are far from the actual condition of the road surface excitation frequency,the wheel loader drive axle housing damage occurred mostly in the low stress amplitude under.